Let's Get Invisible! - Stine, R. L. (New York Scholastic, 1998)
Max discovers a magic mirror in the attic that can make him become invisible. But each time he becomes invisible he stays that way longer and longer until he feels he's losing control.
Keywords: Horror stories -- Juvenile fiction